Prevalence of Stroke Among Chinese, Malay, and Indian Singaporeans - Narayanaswamy Venketasubramanian; Louis Tan; Suresh Sahadevan; Jing Jih Chin; Ennapadam S. Krishnamoorthy; Ching Ye Hong; Seang‐Mei Saw (2005)
Stroke prevalence data among mixed Asian populations are lacking. Prevalence rates of stroke were studied among Singaporeans aged > or =50 years of Chinese, Malay, and Indian origin.Study participants were selected by disproportionate stratified random sampling by race. Trained interviewers performed face-to-face interviews with subjects using the World Health Organization screening protocol for neurological diseases. Data were also collected on a self-report of stroke. Subjects suspected to have had a stroke underwent a clinical evaluation to diagnose or exclude stroke. Case notes review was performed for those who were unable to come for clinical evaluation.The study involved 14 906 participants: 6734 men, 8172 women, age range 52 to 106 years, Chinese:Malay:Indian ratio 3:1:1. Participation rate was 66.9%. Six hundred and six were diagnosed to have a stroke, yielding a crude prevalence rate of 4.05% (95% CI, 3.75 to 4.38) and a World Health Organization world population age-gender-standardized rate of 3.65% (95% CI, 3.36 to 3.96). Prevalence rates rose with age (P<0.001 for trend) and were higher among men compared with women, 4.53% (95% CI, 4.05 to 5.07) versus 2.91% (95% CI, 2.57 to 3.29), P<0.01. Age and gender-standardized rates among Chinese, Malays, and Indians were 3.76% (95% CI, 3.38 to 4.17), 3.32 (95% CI, 2.72 to 4.07), and 3.62% (95% CI, 2.95 to 4.44), respectively, P>0.2. Prevalence was highest among Chinese men at 4.78% (95% CI, 4.14 to 5.50) and lowest among Malay women at 2.81% (95% CI, 2.08 to 3.81), P=0.01.There is no difference in stroke prevalence among Chinese, Malay, and Indian Singaporeans. Prevalence is highest among Chinese men and lowest among Malay women. The reasons for these differences warrant further investigation.